EFFECTIVITY OF MULTIFUNCTION HERBAL TOOTHPASTE CONTAINING BAY LEAF (EUGENIA POLYANTHA WIGHT) EXTRACT AS EXTRINSIC STAIN REMOVAL ON TEETH AND DENTURE - Mutiara Annisa; Archadian Nuryanti; Anne Handrini Dewi (Odonto : Dental Journal, 2022)
Background: White teeth colour influence aesthetical appearance which leads to self-confidence and quality of life. Extrinsic stain is the most common aetiology of teeth discoloration, which caused by widely consumed products such as tea, coffee, and tobacco. It also formed on denture and cause negative impacts. Commercial extrinsic stain removal toothpastes only indicated for teeth and contain chemical active agent with undesirable effects. Aim of this study is to determine effectivity of bay leaf (Eugenia polyantha Wight) extract as toothpaste active agent for extrinsic stain removal on teeth and dentures.Method: Pictures of teeth, artificial teeth, and acrylic resin base taken before experiment, after stain induction (using 25g of tea in 100ml of 100oC water for 7 days, tea solution replaced every 24 hours), and after brushing. Toothpastes used for brushing were no active agent basic formulation toothpaste, bay leaf extract toothpastes at 5%, 10%, 15% concentrations, and commercial stain removal toothpaste as positive control. Specimens were brushed using automatic brushing machine for 70 seconds/surface, using 250g load, and speed 5 movements/sec. Colour index analysis of specimens’ pictures were computerized and analysed using CIELAB method to obtain L-value of extrinsic stain removal. Data analysis performed using one-way ANOVA (α=0.05).Result: There is effect of toothpaste containing bay leaf extract 15% to remove extrinsic stain both on teeth, artificial teeth, and acrylic resin base according to one-way ANOVA.Conclusion: Bay leaf extract is effective and potential to be used as toothpaste active agent for extrinsic stain removal on teeth and denture.